If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 4)(X + 3) = 0 Reorder the terms: (4 + x)(X + 3) = 0 Reorder the terms: (4 + x)(3 + X) = 0 Multiply (4 + x) * (3 + X) (4(3 + X) + x(3 + X)) = 0 ((3 * 4 + X * 4) + x(3 + X)) = 0 ((12 + 4X) + x(3 + X)) = 0 (12 + 4X + (3 * x + X * x)) = 0 (12 + 4X + (3x + xX)) = 0 (12 + 4X + 3x + xX) = 0 Solving 12 + 4X + 3x + xX = 0 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + 4X + 3x + -12 + xX = 0 + -12 Reorder the terms: 12 + -12 + 4X + 3x + xX = 0 + -12 Combine like terms: 12 + -12 = 0 0 + 4X + 3x + xX = 0 + -12 4X + 3x + xX = 0 + -12 Combine like terms: 0 + -12 = -12 4X + 3x + xX = -12 Add '-3x' to each side of the equation. 4X + 3x + -3x + xX = -12 + -3x Combine like terms: 3x + -3x = 0 4X + 0 + xX = -12 + -3x 4X + xX = -12 + -3x Reorder the terms: 12 + 4X + 3x + xX = -12 + -3x + 12 + 3x Reorder the terms: 12 + 4X + 3x + xX = -12 + 12 + -3x + 3x Combine like terms: -12 + 12 = 0 12 + 4X + 3x + xX = 0 + -3x + 3x 12 + 4X + 3x + xX = -3x + 3x Combine like terms: -3x + 3x = 0 12 + 4X + 3x + xX = 0 The solution to this equation could not be determined.
| 7x+12=5x-4 | | -4x^2+19x-21=0 | | 240=x^2+22x | | 5(x-2)= | | (2a-5)-(3a+1)= | | 2(3w+2)-12=3w-11 | | 6r+2=56 | | 2x+x+x=180 | | 3(w-6)-5w=-36 | | h=-5t^2+60t | | 7x+3x+90=180 | | -16t^2+24t+3=12 | | X^3-9x^2+20x-12=0 | | 3x(x-9)= | | 3+2t=13 | | 5x-2= | | 3x^3+3x^2-11x-10=0 | | 4.2(x-1)=9.8 | | (x)(x)(x)+4(x)(x)-25x-100=0 | | 25x-10= | | x^2+5x=x(x-11) | | -12=-7-3.5s | | 7xy+1xy=72 | | (x)(x)(x)+4(x)(x)-100=0 | | 6x+10= | | n=wsv | | 7(a+1)-3a=5+4(a-1) | | 2(x-7)=3 | | -18y=da | | 1.33x+2=-1 | | 1.33+2=-1 | | 2*-8.5+13.6=0.4*-8.5 |